PENGARUH MEKANISME GOOD COORPORATE GOVERNANCE TERHADAP PROBABILITAS PADA INDUSTRI PERBANKAN LISTING DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Sulistyoningsih Sulistyoningsih; Gideon Setyo B. (Jurnal Riset Akuntansi dan Bisnis, 2016)
Good Corporate Governance is a non-financial factors that can affect positively on the performance of the company. This study aimed to examine the effect number of people in the board of directors, board of commissioners, audit committee, external audit quality and firm size on the profitability of the banking company listed on the Stock Exchange in the period 2011-2015. These results indicate that the size of the board of directors and external audit quality have significant positive effect on profitability. While the size of the board of commissioners, audit committee size and total assets have not significant positive effect on profitability. Simultaneously a significant difference between the size of the board of directors, board of commissioners, the size of the audit committee, external audit quality, and total assets of profitability in the banking industry listing on the Indonesia Stock Exchange with a coefficient of determination is 24.1%